Economics : principles, problems, and policies - McConnell, Campbell R.; Brue, Stanley L. (Boston, MA : Irwin/McGraw-Hill, 1999)
The book provides a basic understanding of economics. This edition has been thoroughly revised, polished and updated with one additional new chapter and three other chapter containing new content, they included Technology, R and D, and efficiency. Extending the analysis of aggregate supply. Disputes in macro theory and policy. Transition economies: Russia and China.
Includes index.
rua 26/02/15
Loans
Keywords: Economics